APLIKASI KEUANGAN SYARIAH PADA PASAR UANG - Nabiil Salasa Ramadhan; Nilam Utami Aqillah; Maryam Batubara (Bajang Institute, 2022)
The money market is a place where surplus and storage parties meet,with short-termnfundsnwithnmaturitiesnofnless then one year.This money market helps to benefit those who do not have money,while those who have enough money get take advantage of the opportunity tonincreasentheirnincomenas wellnasntonreduce the risk to theirnfinances